Diversity of Microfungi in a High Radon Cave Ecosystem - Martin-Pozas, Tamara; Nováková, Alena; Jurado, Valme; Fernandez-Cortes, Angel; Cuezva, Soledad; Saiz-Jimenez, Cesareo; Sanchez-Moral, Sergio (Frontiers in Microbiology, 2022)
Castañar Cave is a clear example of an oligotrophic ecosystem with high hygrothermal stability both seasonal and interannual and the particularity of registering extraordinary levels of environmental radiation. These environmental conditions make the cave an ideal laboratory to evaluate both the responses of the subterranean environment to sudden changes in the matter and energy fluxes with the exterior and also any impact derived from its use as a tourist resource under a very restrictive access regime. In 2008 a fungal outbreak provoked by a vomit contaminated the sediments which were removed and subsequently treated with hydrogen peroxide. Fungal surveys were carried out in 2008 and 2009. The visits were resumed in 2014. Here, twelve years after the outbreak, we present an exhaustive study on the cave sediments in order to know the distribution of the different fungal taxa, as well as the prevalence and spatio-temporal evolution of the fungi caused by the vomit over the years under the conditions of relative isolation and high radiation that characterize this cave.